PENERAPAN METODE PEMBELAJARAN AKTIF TIPE COURSE REVIEW HOREY TERHADAPPEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIIISMPN 23 PADANG - Selviora, Ria Okta; Febriana, Rina; Cesaria, Anna (Pendidikan Matematika, 2014)
ABSTRACTÂ This study was motived by an understanding of mathematical concepts students are still low. This study aims to determine whether studentsâ understanding of mathematical concepts by applying active learning methods type course review horey better than studentsâunderstanding of mathematical concepts by applying conventional learning class VIII SMPN 23 Padang. This research was an experimental research with randomized research design of the subject.The research instrument was the final test. From of the test used was the essay with reliability=0,75. The result obtained from testing the hypothesis t = 3,5194 and t table = 1,677, because t count> t table thenIt can be concluded that the studentsâ understanding of mathematical concepts by applying active learning method type course review horey better than conventional teaching class VIII SMPN 23 Padang with a confidence level of95 %( .